Dampak Pandemi Covid-19 Terhadap Sikap Pembelajaran Bahasa Pada Mahasiswa Universitas Mitra Karya Bekasi - Tiara Noviarini (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to determine the impact of the Covid-19 conditions on the learning attitudes of Language students at Mitra Karya University Bekasi. This study uses a questionnaire that has been distributed to 100 Umika students to measure the level of student behavior. The result of this research is that virtual learning has a positive effect on student attitudes. The students are showing enthusiasm in their studies, and they welcome distance learning in the current COVID-19 pandemic. Most students like online teaching because it is a new and exciting experience for them. When studying online, students seem very excited and comfortable.